The Campus Canopy, 1934-11-21 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1934)
Temple and Pardee Heard in Recital; French Club Progresses; Dr. W.A. Smart Pays Annual Visit; Gilmer Speaks; Amplifier is Purchased; Ali Baba To Be Presented; Dr. Marian Farbar Addresses Classes;
### Persons Mentioned ### Ali Baba; Alimae Temple; Anna Mae Wong; Annie Kate Knight; Billie Ham; Bobby Cochran; Broun Hutchinson; Cesar Frank; Chappie Bragg; Clara Davis Adams; Clara Louise Driskell; Clare Lawson; Cleo Barber; Doris Swindle; Doris Young; Dorothy Ogle; Dr. Smart; E. Warren; Estelle Roberts; Esther Smith; Evelyn May; Frances Garbutt; Frances Pardee; Franklin; G. Henri Duvernors; George Raft; Gertrude Gil; Gertrude Gilmer; Grace Lahey; Harold Gulliver; Harry Kitson; Helen Claire Varne; Henry Kate Gardner; I. A. Ben; Jeselyn Moseley; Jessie Catledge Langdale; Johnnie Mae Kelley; Kathryn Morgan; Kent Taylor; Leila Urquahart; Leonora Dufour; Leonora DuFour; Leonora Ivey; Louise Driskell; Lucille Tyson; Lucy Hammond; Madame Sourcier; Mamie Register; Margaret Carter; Margaret Hudson; Marian Farbar; Marie Galante; Marion Reid; Marjorie Groover; Mary Alderman; Mary Nell Carlyle; Maud Hilley; Mildred Turnbull; Miriam Hopkins; Pierrette; Pinky Odom; Ruby Harrison; Ruth Williams; Sadie McKee; Sarah Rachel Cox; Tim McCroy; Una Ritch; Virginia Sheppard; Vonice Ritch; W. A. Smart; Willene Roberts; ### Locations Mentioned ### America; Atlanta, Georgia; Chicago, Illinois; Emory; Georgia; India; Jesup, Georgia; Lakeland, Georgia; Lombardy; Milledgeville, Georgia; Patterson Street, Valdosta, Georgia; Quitman, Georgia; Ray City, Georgia; West Hall Rotunda(Georgia State Womans College); Savannah, Georgia; South Georgia; Thomasville, Georgia; Treasure Island; Valdosta, Georgia; Virginia; Waycross, Georgia; ## Organizations Mentioned ## Air Swanson; Amoco; Buskin Dramatic Club; C. C. Varnedoe & Co; Emory University; French Club; Georgia State Womans College; Home Economics Department; International Relations Club; Junior House; La Dame de Bronze; Mathis & Youmans Co; McDonalds; Mercer'Clemson; Ritz; Science'Math Club; Shell; University of Georgia; Valdosta Club;
Keywords: Georgia State Womans College -- Students -- Periodicals; College student newspapers and periodicals -- Georgia -- Valdosta; Newspapers